Menyewakan Kembali Objek Sewaan dalam Kajian Filsafat Hukum Islam - Firdaus, Zulkifli; Busyro, Busyro (Fakultas Syariah Institut Agama Islam Negeri Lhokseumawe, 2023)
One of the requirements of the leased object is that the object is perfectly owned by someone. In some cases, a person who rents a certain object sometimes rents it back to others even though he is not the owner, only as a beneficial owner. This paper aims to examine the acquisition of property obtained as a result of renting out the leased object from the perspective of hifz al-mal which is part of the discussion of maqashid al-syariah (philosophy of Islamic law). This research uses the library research method by collecting existing data from various related literature, then it is described and analyzed objectively with the maqashid al-syariah theory in the field of hifz al-mal. The results showed that re-renting a rented object without the permission of the object owner is a prohibition of Islamic law in obtaining property at the al-hajiyah level which makes it haram to do so, as well as the property obtained from these activities. Therefore, this action must be stopped to realize the benefit of the acquisition of property.